Guía para diagnóstico y tratamiento de la Enfermedad de Gaucher - Colquicocha-Murillo, Maria; Cucho-Jurado, Janetliz; Eyzaguirre-Zapata, Renee Mercedes; Manassero-Morales, Gioconda; Moreno-Larrea, Mariela del Carmen; Salas-Arbizu, Katia Liliana; Torres-Argandoña, Aimee Margarita; Vargas-Castro, Jesús Olga (Revista Médica Herediana, 2015)
A este articulo no le corresponde Resumen.